Pembelajaran Ekoteologi pada Sentra IMTAQ Islam di Taman Kanak-Kanak Plus Puri Kencana Samarinda - Qamariah, Sa'da; Robingatin, Robingatin (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
This study aims to analyze the implementation of eco-theological values in the Islamic IMTAQ Learning Center as an effort to strengthen moral and religious development in early childhood education at Puri Kencana Kindergarten, Samarinda. Using a qualitative descriptive field research approach, the study involved the principal, IMTAQ teachers, children, and parents. Data were collected through participatory observation, in-depth interviews, and documentation. The findings reveal that eco-theological values, tauhid-based awareness of God’s creation, human responsibility as khalifah, and environmental care are systematically integrated into IMTAQ learning activities through habitual prayers, hygiene practices, plant care, and Qur’an-Hadith-based spiritual reflections. These practices contribute to the development of children’s moral qualities, including honesty, discipline, responsibility, and empathy, as well as religious attitudes such as gratitude, worship, obedience, and social concern. Theoretically, this study proposes an eco-theological learning model for Islamic early childhood education that bridges normative Islamic environmental ethics with center-based pedagogical practices. The findings support eco-theology-based IMTAQ learning as a viable approach to fostering religious character and ecological awareness from an early age.